The Influence of Work Skills and Work Environment on Employee Work Productivity at The Niks Konveksi Company - Mustofa, Adelia Nava Ulfa; Asmawan, Moh Chairil (Universitas Muhammadiyah Surakarta, 2024)
The aim of this research is to determine the influence of work skills and work environment on work productivity. This research uses a quantitative method using primary data obtained through distributing questionnaire data. The population in this study were all Niks Konveksi employees, totaling 80 employees. The number of samples from this research was 66 respondents. Based on the research results, it was found that the work skills variable had an effect on work productivity. This can be seen from the calculated t value of 6.109 , which means 6.109 > 1.996 and the significance is 0,000 < 0.05 . Work environment variables partially influence work productivity. This can be seen from the calculated t value of 3.735 , which means 3.735 > 1.996 and significance 0,000 < 0.05 . Furthermore, the variables of work skills and work environment simultaneously influence productivity. This can be seen from the calculated F value which is 197.775 , which means 197.775 > 3.14 and significance 0,000 < 0.05 .